2003
DOI: 10.1038/sj.ejcn.1601577
|View full text |Cite|
|
Sign up to set email alerts
|

Bone and nutrition in elderly women: protein, energy, and calcium as main determinants of bone mineral density

Abstract: Objective: Nutrition is an important factor in the prevention and treatment of osteoporosis. Our goal was to examine the relationship between various nutrients and bone mass of several skeletal sites in elderly women, taking into account possible confounding variables. Design/methods: A cross-sectional study in 136 healthy Caucasian, postmenopausal women, free of medications known to affect bone was carried out. Bone mineral density (BMD) and body composition (lean and fat tissue) were measured by dual X-ray a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
96
2
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(104 citation statements)
references
References 41 publications
2
96
2
4
Order By: Relevance
“…Energy intake is related to body size, physical activity and weight variations that influence BMD, which is why previous authors found significant relationship between BMD and energy intake (Ilich et al, 2003). No such relationship appears in our study, probably due to the highly variable levels of physical activity thermogenesis in the elderly, and also to differences in body size: among subjects with the same BMI, those who are taller and heavier have a higher energy intake, but they might have the same BMD.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Energy intake is related to body size, physical activity and weight variations that influence BMD, which is why previous authors found significant relationship between BMD and energy intake (Ilich et al, 2003). No such relationship appears in our study, probably due to the highly variable levels of physical activity thermogenesis in the elderly, and also to differences in body size: among subjects with the same BMI, those who are taller and heavier have a higher energy intake, but they might have the same BMD.…”
Section: Discussionmentioning
confidence: 94%
“…Understanding the effect of potentially modifiable lifestyle factors on BMD in the elderly is essential to osteoporosis prevention and treatment; among these factors, sarcopenia and nutritional disorders may have a key role (Ilich et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(dietary and supplemental) vitamin C intake has not been linked with BMD in women (83,84,88) ; and 324 both positive and negative associations have been reported in men (74) , although the latter findings previously been shown to be significantly lower in smokers than non-smokers (65) and serum vitamin 327 C levels are lower in smokers independent of dietary intakes (64,65) . Hence, the exclusion of smokers 328 to the study may have led to more consistent findings.…”
mentioning
confidence: 68%
“…Although positive associations between dietary 318 vitamin C intake and supplements and bone density have previously been reported, findings have 319 been inconsistent (8,9,74,(83)(84)(85) . (6,8,11,74,84,86,87) , three to seven-day food diaries (9,88) and 24-hour recalls (12,83) . Moreover, total…”
mentioning
confidence: 99%